Women Empowerment through Entrepreneurship: A case study of Dalla Gaaun home stay - K.C., Govinda (Journal of Entrepreneurship & Management Studies, 2024)
In countries like Nepal women are confined with the four walls of their homes. In ethnic community of rural area women are deprived from social, economical, political and personal rights. Women entrepreneurship is one of the many tools to empower not only economically but also personally, socially and politically. This study was conducted in one of the least developed district of Nepal, Bardiya. Study was focused on Tharu community Dalla Gaaun Home stay. Study was conducted in November (5-7) 2020 for three days. These home stays are operated by Tharu community which is indigenous community of Nepal. Researchers used number of tools to collect the data of population. Unstructured questionnaire were also prepared for the evidence and were filled by closely observing the respondents. Entrepreneurship really empowered the women of Dalla Gaaun home stay economically, personally, socially and politically.